2008
DOI: 10.1016/j.vetmic.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ɛ-toxin from Clostridium perfringens in the nervous system

Abstract: Epsilon-toxin (epsilon-toxin), produced by Clostridium perfringens type D, is the main agent responsible for enterotoxaemia in livestock. Neurological disorders are a characteristic of the onset of toxin poisoning. Epsilon-Toxin accumulates specifically in the central nervous system, where it produces a glutamatergic-mediated excitotoxic effect. However, no detailed study of putative binding structures in the nervous tissue has been carried out to date. Here we attempt to identify specific acceptor moieties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 20 publications
(19 reference statements)
4
93
1
Order By: Relevance
“…To overcome this obstacle, we expressed, purified, and trypsin-treated a GFPtagged form of the wild-type ⑀-toxin (5,33,34). Remarkably, this toxin retains cytotoxic activity, and the GFP tag is not lost following trypsin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this obstacle, we expressed, purified, and trypsin-treated a GFPtagged form of the wild-type ⑀-toxin (5,33,34). Remarkably, this toxin retains cytotoxic activity, and the GFP tag is not lost following trypsin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This placed the etxB gene under the regulation of the bacteriophage T7 RNA polymerase and fused the N-terminal end of the prototoxin to the pelB leader peptide and the C-terminal end of the prototoxin to a His 6 affinity tag (to aid in purification of the protein). A derivative plasmid that expressed a GFP-⑀-toxin fusion protein was also constructed (5,33,34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxin's potential targets include vascular endothelia, synaptosomal membrane fractions, astrocytes, microglial cells, and myelin (Soler-Jover et al, 2004Dorca-Arévalo et al, 2008). The major manifestations of epsilon neurotoxicity are microvascular endothelial injury and vasogenic edema (Ghabriel et al, 2000;Finnie et al, 1999Finnie et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…When mice were injected intravenously with labeled, functional ε-toxin, it was found to accumulate on endothelia in various organs, especially the kidneys and brain (401,402). In the nervous system, ε-toxin associates with myelin structures (403). Although the neurotoxic effects were initially hypothesized to be caused by damage to brain blood vessels, later work showed that ε-toxin is also able to directly attack brain oligodendrocytes (82).…”
Section: Pft-induced Barrier Dysfunctionmentioning
confidence: 99%